Amino‐Acid‐Based Chiral Nanoparticles for Enantioselective Crystallization. (21st March 2015) - Preiss, Laura C.; Werber, Liora; Fischer, Viktor; Hanif, Sadaf; Landfester, Katharina; Mastai, Yitzhak; Muñoz‐Espí, Rafael
<x xml:space="preserve">Abstract</x> Chiral polymer nanoparticles based on amino acids are prepared by miniemulsion polymerization and are demonstrated to serve as nucleating agents for the enantioselective crystallization of racemic mixtures of amino acids. The synthesized chiral nanoparticles are suited for the development of enantioselective processes and also contribute to a better understanding of chiral recognition on polymer surfaces.